Pro ASP.NET 4.5 in C# - Freeman, Adam.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
ASP.NET 4.5 remains Microsoft's preferred technology for creating dynamic websites, providing developers with unrivaled power and flexibility. Pro ASP.NET 4.5 in C# is the most complete reference to ASP.NET that you will find. This comprehensively revised fifth edition will teach you everything you need to know in order to create well-designed ASP.NET websites. Beginning with core concepts the book progresses steadily through key professional skills. You'll be shown how to query databases in detail, consider the myriad applications of XML, and step through all the considerations you need to be aware of when securing your site from intruders. Finally, you'll consider advanced topics such as using client-side validation, jQuery and Ajax. By the time you have read this book you will have learned all the skills you need to use ASP.NET 4.5 with confidence.
Keywords: Computer science; Computer Science; Computer Science, general